THE EFFECT OF ACCOUNTABILITY AND TRANSPARENCY ON ASSET MANAGEMENT AT THE BPKD OF BIREUEN DISTRICT - Nurul Azmi; Rozana Putri; Saryati (RADJA PUBLIKA, 2024)
Assets refer to economic resources controlled or owned by the government as a result of past events. From these assets, it is hoped that economic and/or social benefits can be obtained in the future, both by the government and society. Asset management is the basis for local governments to manage their assets, this has an impact on increasing the function of the assets themselves, both in terms of the number and value of the assets. The aim of this research is to test and determine how accountability and transparency influence asset management at the Bireuen Regency BPKD. The population in this study were all employees in the Bireuen Regency BPKD, totaling 110 people. Based on the calculations above, the sample of respondents in this study was adjusted to 53 people from the total number of BPKD employees in Bireuen Regency. Based on the research results, it is known that the t-test results for the accountability variable (X1) obtained a tcount of 3.061 with a significant level of 0.003 and for the Transparency variable (X2) obtained a tcount of 2.148 with a significant level of 0.005. The results of the F test in this study obtained an Fcount value of 5.582 with a significance level of 0.001. Meanwhile, the Ftable value has a significance level of 5% and df = nk-1 (53 – 2 – 1 = 50), the Ftable value is 2.56. Thus, Fcount> Ftable means that simultaneously accountability and transparency have a significant effect on asset management at the Bireuen Regency BPKD.